Utilization of Corn Waste: A Learning Media Based on Madurese Local Wisdom to Stimulate Children's Symbolic Thinking - Adhani, Dwi Nurhayati; Fitri , Fitri; Nazarullail , Fikri; Abdul Latif, Muhammad (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
The utilization of corn waste in education, particularly in early childhood education, offers various benefits, including the development of learning media. This study aims to analyze the use of corn waste in stimulating symbolic thinking skills in children aged 5-6 years. The research employs a qualitative method with a case study approach. The subjects include children from group B and educators at TK Muslimat NU Siti Fatimah Bangkalan. Data collection techniques encompass passive participant observation, semi-structured interviews, and documentation. Data analysis follows the model developed by Miles and Huberman. The results indicate that symbolic thinking skills can be stimulated using magazines, posters, and educational toys. Additionally, corn waste media also stimulate children's symbolic thinking skills by utilizing corn kernels, husks, and cobs. This study provides an alternative child-friendly medium by leveraging natural resources such as corn to stimulate symbolic thinking in early childhood. Therefore, this research aids educators in developing affordable and environmentally friendly learning media. The use of corn waste not only offers a creative solution in learning but also supports environmental conservation efforts through the use of readily available natural materials. Using corn kernels, husks, and cobs as learning media demonstrates that materials often considered waste can have significant value in the educational context. Consequently, it is crucial for educators to continuously seek and develop innovative and sustainable learning media, harnessing the potential of local resources available in their surroundings.